Flexural, Impact and dynamic mechanical analysis of hybrid composites: olive tree leaves powder/ pineapple leaffibre/epoxy matrix - Senthilkumar, K.; Chandrasekar, M.; Alothman, Othman Y.; Fouad, Hassan; Jawaid, M.; Jawaid, M. (Elsevier, 2022)
The objective of this work is to determine the suitability of olive tree leaves powder (OTL) as reinforcement along with pineapple leaf fibre (PALF) in the epoxy composites. The parent and hybrid composites were fabricated using the hot press technique with the overall fibre loading at 40 wt% and OTL: PALF in the ratio of 50:50, 30:70 and 70:30, respectively. The fabricated composites were characterized using dynamic mechanical analysis (DMA), flexural and impact tests. As the proportion of PALF was increased in the hybrid composites, impact strength improved significantly. However, hybrid composites were not effective in withstanding the bending load where their bending strength and flexural modulus were lower than the parent composites. Hybrid composites outperformed parent composites with superior storage modulus, lower loss modulus and lower damping factor as per the DMA results.